179 Safety and Feasibility of Platelet-Rich Plasma Injections for Peyronie's Disease: Update From a Single-center Double-blind Placebo-controlled Randomized Trial. Issue 1 (1st April 2022) - Chu, K.; Masterson, T.; Efimenko, I.; Molina, M.; Saltzman, R.; Ibrahim, E.; Ramasamy, R.
ABSTRACT: Introduction: Peyronie's Disease (PD) is prevalent in approximately 7.1% of the general population. Current treatment approaches include medical therapy and surgical intervention, and intervention only occurs once the disease process has entered the chronic, stable phase. The only FDA-approved medical therapy involves use of intralesional collagenase clostridium histolyticum injection and surgical interventions include tunica albuginea plication, plaque excision without grafting, or placement of penile prothesis. Additional PD therapies are needed as current treatment modalities have limited efficacy and considerable side effects. Platelet-derived therapies have seen increased use across various specialties in medicine, especially in orthopedics, due to their potential ability in wound healing and tissue regeneration. As calcified scar plaques are frequently identified in PD patients, autologous platelet rich plasma (PRP) may prove to be a viable treatment for this patient population. Objective: We reviewed an initial series of patients receiving PRP vs placebo for PD to assess safety and feasibility among men recruited in a double-blind placebo controlled single-center clinical trial. Methods: We reviewed data for men recruited into the clinical trial treated with PRP vs placebo at our center from April 2021 to July 2021. Patients were observed immediately post-injection and at follow-up for complications and tolerability. Where applicable, International Index of Erectile Function (IIEF-5) scores were reviewed before and after injections for PD. Results: We report data from the men who have completed 2 completed injections (PRP or placebo). No post-procedural minor adverse events were seen in any of the men. None of them reported adverse effects such as penile bruising, swelling, edema, allergy, penile fracture, or mild pain at injection site. No patients experienced complications at follow-up. No worsening curvature was observed in men completing pre/post evaluations. Conclusions: PRP appears to be a safe and feasible treatment modality in patients with PD from our limited data accumulated thus far in our ongoing randomized placebo-controlled trial with PRP for PD. Our study is the first study in the USA accruing men with PRP for PD and believe that safety and efficacy data accumulated from our study will be important for patient counseling. Disclosure: No